Early appendectomy shortens antibiotic course and hospital stay in children with early perforated appendicitis - Hsin-Yu Tsai; Hsun-Chin Chao; Wan-Ju Yu (Elsevier, 2017)
The optimal management of perforated appendicitis in the pediatric population has been controversial. This study aimed to compare the therapeutic efficacy between conservative treatment (CS) and early appendectomy (EA) in pediatric perforated appendicitis, and to determine whether surgical intervention is an optimal treatment modality for early perforated appendicitis in children. Methods: Patients treated between January 2012 and April 2014, aged 0-18 years, with an imaging-based diagnosis of perforated appendicitis were retrospectively reviewed. Patients were classified into nonabscess and abscess groups by image findings, and were further categorized into CS and EA groups by treatment modality. Early perforated appendicitis was defined as having duration of symptoms≤7 days, C-reactive protein level≤200 mg/L, maximum abscess diameter≤5 cm, and absence of general peritonitis, and unstable vital signs. The clinical features and therapeutic outcomes were compared between CS and EA in each group. Results: A total of 326 patients had confirmed appendicitis, including 116 patients with an image diagnosis of perforation. The CS group had a significantly longer duration of symptoms, larger abscesses, and higher serum C-reactive protein levels at presentation (all p<0.05). Patients in the EA group had a shorter antibiotic course and length of hospitalization, and a lower rate of antibiotic escalation than those in the CS group (p<0.001, p<0.001, and p<0.05, respectively). In patients with early perforated appendicitis, the CS and EA groups showed no difference in baseline disease severity. Patients in the EA group also had a shorter antibiotic course and length of hospitalization than those in the CS group (p<0.001 and p<0.001, respectively). Conclusion: Compared with CS, EA shortens the antibiotic course and hospital stay in pediatric early perforated appendicitis, even in the presence of small abscesses.